Histopathologic changes in soft tissue associated with radiographically normal impacted third molars - Kotrashetti Vijayalakshmi; Kale Alka; Bhalaerao Sudhir; Hallikeremath Seema (Wolters Kluwer Medknow Publications, 2010)
Background: The incidence of impacted or embedded third molars accounts for approximately 98%. Since 1948, there are studies reporting pathological changes in an asymptomatic dental follicle. Controversy still exists for removal of asmptomatic impacted teeth. Hence, this study was performed to histologically evaluate soft tissue pathosis in the pericoronal tissues of impacted third molars with pericoronal radiolucency measuring up to 2.5 mm on orthopantomographs. Materials and Methods: Forty-one asymptomatic impacted third molars with follicular space of up to 2.5 mm on radiographs were included. The disimpacted teeth and the follicular tissues were obtained for histological examination. Results: Age of the patients ranged from 14 to 25 years. Of 41 tissues evaluated, histopathological reports of 18 follicles were suggestive of dentigerous cyst, two follicles showed odontogenic keratocyst, one follicle each of calcifying epithelial odontogenic cyst, ameloblastoma-like proliferation, odontogenic myxoma and odontogenic fibroma. Conclusion: This study showed 58.5% of asymptomatic cases with definite pathological changes. Hence, thorough clinical and radiographic examination should be carried out for all impacted third molars and the dental follicular tissue should be submitted for histopathological evaluation.